Platelet Membrane Receptor Proteolysis: Implications for Platelet Function - Wu, Jiayu; Heemskerk, Johan W. M.; Baaten, Constance C. F. M. J. (Frontiers in Cardiovascular Medicine, 2021)
The activities of adhesion and signaling receptors in platelets are controlled by several mechanisms. An important way of regulation is provided by proteolytic cleavage of several of these receptors, leading to either a gain or a loss of platelet function. The proteases involved are of different origins and types: (i) present as precursor in plasma, (ii) secreted into the plasma by activated platelets or other blood cells, or (iii) intracellularly activated and cleaving cytosolic receptor domains. We provide a comprehensive overview of the proteases acting on the platelet membrane. We describe how these are activated, which are their target proteins, and how their proteolytic activity modulates platelet functions. The review focusses on coagulation-related proteases, plasmin, matrix metalloproteinases, ADAM(TS) isoforms, cathepsins, caspases and calpains. We also describe how the proteolytic activities are determined by different platelet populations in a thrombus, and conversely how proteolysis contributes to the formation of such populations.